2016
DOI: 10.1016/j.jconhyd.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous anaerobic transformation of tetrachloroethene and carbon tetrachloride in a continuous flow column

Abstract: Tetrachloroethene (PCE) and carbon tetrachloride (CT) were simultaneously transformed in a packed column that was bioaugmented with the Evanite culture (EV). The data presented here have been obtained over a period of 1930days. Initially the column was continuously fed synthetic groundwater with PCE (0.1mM), sulfate (SO4(2-)) (0.2mM) and formate (2.1mM) or lactate (1.1mM), but not CT. In these early stages of the study the effluent H2 concentrations ranged from 7 to 19nM, and PCE was transformed to ethene (ETH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“… 6 Carbon tetrachloride (CT) and especially CF have been observed to inhibit the reductive dehalogenation of perchloroethylene (PCE) and trichloroethylene (TCE). 7 Hence, a better understanding of mixed CHC transformation under laboratory conditions may provide a basis for groundwater remediation when multiple contaminants are present.…”
Section: Introductionmentioning
confidence: 99%
“… 6 Carbon tetrachloride (CT) and especially CF have been observed to inhibit the reductive dehalogenation of perchloroethylene (PCE) and trichloroethylene (TCE). 7 Hence, a better understanding of mixed CHC transformation under laboratory conditions may provide a basis for groundwater remediation when multiple contaminants are present.…”
Section: Introductionmentioning
confidence: 99%
“…9 CT has been anaerobic biotransformed under sulfate-reducing, methanogenic, nitrate-reducing, iron-reducing, fermenting, and mixed electron acceptor conditions. 10 M. F. Azizian 11 et al reported that the simultaneous anaerobic transformation of tetrachloroethene (PCE) and CT in a continuous ow column that was bioaugmented with the Evanite culture (EV). Additionally, CT biodegradation under denitrication conditions is of particular interest because of the simultaneous occurrence of both CT and nitrate in groundwater.…”
Section: Introductionmentioning
confidence: 99%
“…Structural and functional dynamics of dechlorinating communities have been investigated in continuous-flow biofilm and packed column systems (Carr et al 1998, Chung et al 2008, Maphosa et al 2010, Sabalowsky et al 2010, Azizian et al 2016, Mirza et al 2016, Mirza et al 2017, Delgado et al 2017. Continuous-flow suspended growth systems have also been used to study the impacts of solids retention times (SRTs) and other critical parameters on dechlorination activity of synthetic consortia and more complex communities (Gerritse et al 1997, Carr et al 2000, Drzyzga et al 2001, Zheng et al 2001, Sabalowsky et al 2010.…”
Section: Introductionmentioning
confidence: 99%